KEEPING PACE WITH GLOBALISATION : INNOVATION CAPABILITY IN KOREA'S TELECOMMUNICATIONS EQUIPMENT INDUSTRY - Sunil Mani (Centre for Development Studies-WP370, 2005)
Korea is one of the four from the developing world to have built up substantial innovation capability in the design and manufacture of state-of-the-art telecommunications equipments. The paper undertakes a detailed review of this innovation capability and analyses its precise status during the time when the Korean economy was subject to a serious financial crisis. The paper maps out the sectoral system for innovation in the telecommunications equipment industry and measures the innovation capability in terms of a set of three separate indicators. The ensuing analysis shows that the country has built up substantial innovation capability in not just fixed telephony but also in mobile communication technologies. There has been some passage of this capability from the public research laboratory to private sector manufacturing firms. The Korean state has continued to support the public laboratory through a variety of financial grants and public technology procurement. However these traditional instruments of support are no longer valid in newer technologies such as mobile telephony. The innovation system has nevertheless achieved considerable sophistication that it is in a position to keep pace with changes in the technology frontier